Innovation networks and the institutional actor-producer relationship in rural areas: The context of artisan food production. (December 2016) - McKitterick, Lynsey; Quinn, Barry; McAdam, Rodney; Dunn, Adele
Abstract: This paper takes a multiple theoretical perspective, utilising concepts from the knowledge exchange and the rural, social networks literatures to explore artisan food enterprise engagement with institutional networks for innovation. A qualitative methodology is adopted, involving semi-structured interviews and group discussions with producers and institutional actors, and participant observation. The findings highlight that while informal networks, including business networks, family associations and international sources play a more important role in innovation for artisan food firms than institutional networks, institutional networks play a critical role in developing social capital and knowledge exchange among producers and in acting as a bridge to informal, embedded networks for these enterprises. The findings demonstrate how sectoral contextual factors shape interactions in the institutional actor-producer relationship, and how they impact upon involvement in institutional networks and in turn facilitate and restrict innovation in this context. Highlights: The sectoral cultural context is critical to an understanding of how rural firms use networks. Informal networks lead to opportunities for radical innovation in artisan food production. Institutional networks play an important role in acting as a bridge to informal, embedded networks. A conceptualisation of social ties in this context should include knowledge derived from non-local territories. Network building can compensate for perceived knowledge gaps from institutional sources.